Enteral formula compared to Nissen-Fundoplication: Data from a retrospective analysis on tolerance, utility, applicability, and safeness in children with neurological diseases - Trovato, Chiara Maria; Capriati, Teresa; Bolasco, Giulia; Brusco, Carla; Santariga, Emma; Laureti, Francesca; Campana, Carmen; Papa, Valentina; Mazzoli, Bianca; Corrado, Silvia; Tambucci, Renato; Maggiore, Giuseppe; et al. (Frontiers in Nutrition, 2023)
Objectives and study Approximately 46–90% of children with neurological disorders (NDs) suffer from gastrointestinal diseases, such as gastro-esophageal reflux disease (GERD), constipation, or malnutrition. Therefore, enteral feeding is often necessary to achieve nutritional requirements. The treatment of GERD could be based on pharmacological therapy, nutritional treatment (changing the type of formula), or surgical treatment (Nissen Fundoplication, NF). The aim of this study was to describe and compare resource consumption between NE based on different formulas and NF in patients with ND. Methods We performed a retrospective analysis on all children with neurological damage (age: 29 days−17 years) treated from January 2009 to January 2019 due to nutritional problems and food and/or gastrointestinal intolerances. For all patients, demographic and anthropometric characteristics, symptoms, type of nutrition (formula and enteral access), and number and type of outpatient or emergency room visits were collected. Patients with <24 months of age at the closing of the database and with <24 months of follow-up were excluded. Results Out of 376 children, 309 children (M: 158; median age: 4 IQR 1–10) were enrolled, among which, 65 patients (NF group M: 33; median age: 5.3 IQR 1.8–10.7) underwent NF. Vomit, GERD, and dysphagia were more represented in the NF group (p < 0.05). Our analysis shows that the NF group seems to present a lower number of hospitalization and a lower number of visits for non-GI disorders, but a higher number of visits for GI disorders compared to non-NF. In the NF group, a higher prevalence of the use of amino-acid-based formula and free diet is observed, with a trend for the lower prevalence of casein-based or whey+casein-based formula (Fisher test p = 0.072). The median cost of a patient enrolled in the database is € 19,515 ± 540 ( 20,742.32 ± 573.96) per year, with no significant difference between the two groups. Regarding formula, at baseline, 76 children consumed a free diet, 24 a casein-based formula, 139 a whey+casein-based formula, 46 a whey-based formula, and 24 an amino-acid-based formula. Conclusions In conclusion, compared to EN, NF may not improve the clinical aspect and related costs in children with NDs. Considering the psychological and QoL burden for patients, in a “step-up” strategy, EN could be proposed as an efficient alternative to NF.